DESIGN OF A PINEAPPLE LEAF FIBER DECORTICATOR MACHINE - Nurhikmah Weisdiyanti; Kiki Santoso; Riri Syavira; Liza Karina Octovyanda Pohan; Rionaldo Tamba; Rita Juliani (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
The manufacture of pineapple leaf fiber decorticator machines has been made in the village of Onan Runggu III, Sipahutar District, North Tapanuli Regency. Machine making aims to help pineapple farmers to overcome the problem of waste and pineapple. The method used starts from feasibility studies, designing machines, collecting and purchasing tools and materials, evaluating results and testing tools. Results obtained by the pineapple leaf fiber decorticator machine 0,12 kg/hour obtained through two stages of grinding namely grinder 1 and grinder 2. The final results obtained from the decorticator machine of pineapple leaf fiber are pineapple leaf fibers that can be used to make raw materials for textile products.